Prevalence and Risk Factors for Symptoms of Attention Deficit and Hyperactivity in Primary Snoring Children - Mei-Ching Chan; Sharon Wan-Wah Cherk; Ka-Li Kwok; Shuk-Yu Leung; Jonathan Pak-Heng Ng; Rachel Shui-Ping Lee; Tracy Man-Kiu Ma (Pediatric Respirology and Critical Care Medicine)
Aim: Primary snoring was reported to affect 7.2% of school children in Hong Kong, and emerging evidence suggested that neurobehavioural symptoms were more frequently found among this group of children. The current study investigated the prevalence of symptoms of attention deficit hyperactivity disorder (ADHD) i.e., attention deficit, hyperactivity and impulsivity (ADHI), in Chinese children with primary snoring. Materials and Methods: Polysomnography results and relevant clinical notes for all Chinese children aged 4–18-year performed from January 2009 to December 2010 in our sleep laboratory were retrospectively reviewed. Data of the Chinese version of modified Epworth Sleepiness Scale and C-domain of Paediatric Sleep Questionnaire were analysed. Results: In primary snorers, the presence of excessive daytime sleepiness (EDS) and higher apnoea–hypopnea index (AHI) were risk factors for symptoms of AD with adjusted odds ratio of 3.2 (95% confidence interval [CI] = 1.2–8.1) and 4.7 (95% CI = 1.1–20.7), respectively. Primary snorer with AD symptoms had higher AHI, 0.32 ± 0.31 compared those without symptoms, 0.21 ± 0.29, P = 0.038. EDS was an independent risk factor for ADHI with odds ratio of 4.7 (95% CI = 1.1–20.0). Conclusion: Early screening for symptoms of ADHD should be performed in children with primary snoring.